Cover Image. Issue 4 (6th February 2022) - Xu, Yuzi; Zhou, Chuan; Li, Jia; Xu, Yangbo; He, Fuming
Abstract : The cover image is based on the Research Article iTRAQ‐based proteomic analysis reveals potential osteogenesis‐promoted role of ATM in strontium‐incorporated titanium implant by Fuming He et al., https://doi.org/10.1002/jbm.a.37345 .